Experience of the employment relationship after a merger - Bennie Linde; René Schalk (Management Revue, 2006)
Mergers and acquisitions create many management challenges. The development of a new employment relationship is one of the problems in such a situation. This paper investigates the influence of previous employment structures and the experience of previous employment relationships on the psychological contract, job satisfaction, job insecurity, and general health of employees in the context of a merged higher education institution. Employees of two previously independent universities that merged into one university completed a questionnaire. The two former universities had a very different history with very dissimilar employment relationships and experiences among personnel. This history influenced the experience of the employment relationship after the merger.
Keywords: 650; employment relations; mergers and acquisitions; work wellness; Arbeitsverhältnis; Arbeitszufriedenheit; Arbeitsplatzsicherung; Übernahme; Südafrika